2022
DOI: 10.3389/fmolb.2022.886904
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis Reveals USP45 as a Novel Putative Oncogene in Pan-Cancer

Abstract: Background: Deubiquitinating enzymes specifically removes ubiquitin molecules from ubiquitin-tagged target proteins, thereby inhibiting the degradation of target proteins and playing an important role in tumor. However, the mechanism of deubiquitinating enzyme USP45 in tumors remains unclear.Methods: Based on the RNA-seq data of tissues and cell lines in The Cancer Genome Atlas (TCGA) database, GTEx and CCLE database, the pan-cancer analysis of USP45 expression and survival outcome were performed using R softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…It has been reported that several DUBs—USP7, USP10, USP33, USP40, USP45, USP46, YOD1, and JOSD1 are involved in carcinogenesis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Moreover, studies have shown that USP7, USP10, USP33, and USP46 are all involved in the progression of colorectal cancer [ 22 , 26 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that several DUBs—USP7, USP10, USP33, USP40, USP45, USP46, YOD1, and JOSD1 are involved in carcinogenesis [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Moreover, studies have shown that USP7, USP10, USP33, and USP46 are all involved in the progression of colorectal cancer [ 22 , 26 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The type and number of immune cells in the tumor microenvironment are related to tumor development and immunotherapy [ 22 ]. Therefore, we utilized the TIMER 2.0 dataset to evaluate the correlation between BCL2A1 expression and immune cell infiltration levels in glioma.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitin speci c peptidase 45 (USP45) is located on chromosome 6q16.2, encoding a deubiquitylase, which is essential for maintaining the DNA repair ability of XPF-ERCC1 [38] . It has been reported that high USP45 expression levels are associated with poor OS in HCC patients by in uencing tumor heterogeneity and tumor stemness [39] . In addition, rs41288947 of USP45 was found to be associated with an increased risk of early-onset arterial coronary disease [40] .…”
Section: Discussionmentioning
confidence: 99%